HOW HUMAN CAPITAL DEVELOPED DURING WORKING LIFE AFFECTS POST-RETIREMENT ACTIVITIES. (11th November 2018) - Willis, R
Abstract: Human capital theory posits that the productivity of individuals in the labor market and in myriad non-market activities (e.g., marriage and childrearing, sports, hobbies, and culture) depends on their stock of human capital. Much of the human capital literature focuses on investments how investments in education, on-the-job training and learning-by-doing lead to the development of general and occupational skills and knowledge that pay off in the labor market. Recent research suggests that working longer may protect against cognitive decline for people in occupations with low cognitive complexity, but that persons who pursued cognitively complex jobs suffer little cognitive decline after retirement. A possible reason for this result those in more complex jobs engage in more complex activities after retirement. This paper will examine the link between pre-retirement occupations and post-retirement activities using HRS data.